Building Entrepreneurship Values Based on Shariah Economic Perspective - Nur Syamsudon Buchori; Johan Budiman; Donny Setiawan; Saipulloh Saipulloh; Ainun Qomaruzzaman; Adiyanto Adiyanto; Mohd Mizan Aslam (Sultan Publisher, 2022)
This research aims to explore the efforts to grow the spirit of entrepreneurship as everyone needs to do it these days. It is caused by an urgent need for someone to get out of economic difficulties. The study was a qualitative approach in the form of library research with qualitative descriptive data analysis. The results of the study showed that shariah economics will reach the goal of life, namely the goal to achieve fallah and maslahah. An entrepreneur thinks of long-term good fortune in both the world and the hereafter and does not only look at the material but also looks at the spiritual. Entrepreneurs will feel the satisfaction of achieving something and fulfilled the needs of life in a balanced way between the world and the hereafter.